Ten Years of Earth and Space Science: Introduction to the Special Collection - Graziella Caprarelli; David Baratoux; Subrahmanyam Bulusu; Cinzia Cervato; Paolo Diviacco; Alina Donea; Steven J. Fletcher; Helen M. Glaves; Cathleen E. Jones; Gaopeng Lu; Astrid Maute; Franklin P. Mills; et al. (Earth and Space Science)
Abstract The journal Earth and Space Science (ESS) was founded in 2014 to offer the scientific community a new platform for the dissemination of key new data, observations, methods, instruments, and models, presented within the context of their application. Thus, the aim of the journal was (and is) to highlight the complexity and importance of experimental design, methodology, data acquisition and processing, intertwined with data interpretation. Such approach is consistent with the mission of most AGU journals, but the distinctive element for ESS is its focus on the concept of the useful impact of publication, progressively replacing that on conventional publication metrics. In this context, the journal has been, since its inception, the preferred home for studies stemming from both global and local geoscience research. This special collection contains 16 papers published in ESS, selected by the Editorial Board to highlight the aims, scope and path of evolution and growth of the journal since it inaugural issue, in 2014.